Factors that influence the provision of MPASI to babies aged less than 6 months at Posyandu Bungalau, Pondok Pucung Village, South Tangerang Regency - Antaria, Abdullah; Dewi Haris, Vera Suzana (Universitas Aisyah Pringsewu, 2024)
approach, namely the dependent variable and the independent variable are measured at the same time. The population in this study were all mothers who had babies aged less than 6 months at Posyandu Bungalau, Pondok Pucung Village, South Tangerang Regency, while the sampling technique used accidental sampling. The research results show the distribution of the frequency of giving MPASI to babies aged less than 6 months, where there are 48 mothers who give MPASI (64.9%), there are 46 mothers who have less knowledge (62.2%), there are 46 mothers who work. 39 people (52.7%), 49 people (66.2%) received family support, 37 people (50%) received influence from the social environment, 42 mothers received the role of health workers (56, 8%). There is a significant relationship between knowledge (Pv = 0.000 with an OR of 132,000), employment (Pv = 0.000 with an OR of 95,000), family support (Pv = 0.000 with an OR of 176.333) and the role of health workers (Pv = 0.000 with an OR of 33.222 ) by giving MPASI to babies aged less than 6 months. Meanwhile, the relationship that was not significant was the social environment (Pv = 0.465 with an OR of 0.621).Conclusions and Recommendations The analysis shows that several factors influence the provision of MPASI to babies aged less than 6 months. It is recommended that parents/mothers increase their knowledge about MPASI through various sources of information. Keywords: MPASI, babies, less than 6 months old